The Relationship of Paramedic Attitude With The Level of Patient Satisfaction in Cendrawasih Dobo Hospital in 2020 - Hidayati, Nurul; Fatmawati, Elis (Jurnal Pendidikan Tambusai, 2021)
Understanding the wishes and desires of customers in this case the patient is an important thing that affects patient satisfaction. Satisfied patients represent a very valuable asset, if they are satisfied they will continue to use the service of their choice, and if they are not satisfied they will tell twice as much to others about their bad experience. The research objective was to determine the relationship between paramedical attitudes and patient satisfaction levels at the Cendrawasih Dobo Hospital, Aru Islands Regency in 2020. Analytical research design with a cross-sectional approach. The population is all hospitalized patients in one month, a sample of some patients who are hospitalized at Cendrawasih Hospital Dobo for at least 3 days sampling technique with purposive sampling. An instrument with a questionnaire. Spearman Rank statistical test data analysis. The results of the study were that patients who came to the MRS at Cendrawasih Hospital Dobo were 60% satisfied and 40% were dissatisfied. The conclusion is that patient satisfaction is a feeling of pleasure, individual satisfaction because of the fulfillment of expectations and desires in receiving health services.